The paradoxes of legitimate EU leadership. An analysis of the multi-level leadership of Angela Merkel and Alexis Tsipras during the euro crisis. Issue 2 (23rd February 2017) - Van Esch, F. A. W. J.
Abstract: In times of crisis, political leaders are torn between calls for strong leadership and the need to maintain their license to operate amongst their constituents. The predicament of European Heads of State and Government (HSG) during crises provides a particularly strong example of this. For on top of the inherent tension between political leadership and democracy, in the European multi-level system, HSG have to balance the demands of many groups of potential followers while facing weak and contradictory vectors of legitimate leadership. This contribution presents a framework by which the inherent tensions of legitimate European leadership may systematically be assessed. It applies this framework to two HSG that were key to the management of the euro crisis, the German chancellor Angela Merkel and the Greek Prime Minister Tsipras in their attempts to walk the tightrope between legitimate and decisive EU leadership.